KEMAMPUAN Bacillus subtilis dan Pseudomonas fluorescens DALAM MELARUTKAN FOSFAT DAN MEMPRODUKSI HORMON IAA (Indole Acetic Acid) UNTUK MENINGKATKAN PERTUMBUHAN TANAMAN TOMAT - Istiqomah Istiqomah; Luqman Qurata Aini; Abdul Latief Abadi (Universitas Tribhuwana Tunggadewi, 2017)
Tomato is an important horticultural commodity in Indonesia and plays strategic role in fulfilling daily needs of the public. The increase in production of tomato can be done by optimizing the provision of nutrients that support growth. The ability of bacteria as biological fertilizer to dissolve phosphate and produce IAA (Indole Acetic Acid) are important criteria for the use of bacteria as agents of plant growth promoters. The purpose of this study was to determine the ability of some isolates of Bacillus subtilis and Pseudomonas fluorescens in dissolving phosphate and produce IAA to enhance the growth of tomato. Phosphate test results showed that all isolates of B. subtilis and P. fluorescens capable of dissolving phosphate with the highest value indicated by P. fluorescens UB-PF5 (18 mm). All isolates of bacteria capable to produce IAA. The resulting value IAA ranged from 0.69 to 1.09 ppm with the highest value produced by B. subtilis UB-ABS2 (1.09 ppm). The test results on the parameters of root weight, root length, plant height and number of leaves showed that tomato treated with B. subtilis and P. fluorescens increased significant growth compared with watering only with distilled water. The highest increased root weight and root length were resulted by P. fluorescens UB-PF5 with values 97.10% and 64.83%, respectively. The highest increased plant height and number of leaves length were resulted by P. fluorescens UB-PF6 with values 38,80% and 30,7%, respectively.